1963
DOI: 10.1002/prac.19630200310
|View full text |Cite
|
Sign up to set email alerts
|

Aminosäureantagonisten. III. ω‐[Bis‐(β‐chloräthyl)‐amino‐benzimidazolyl‐(2)]‐propion‐ bzw. ‐buttersäuren als potentielle Cytostatika

Abstract: Es wird die Synthese von ω‐[Benzimidazolyl‐(2)]‐propion‐ bzw. ‐buttersäuren beschrieben, die in 5‐Stellung durch eine Stickstofflostgruppe und in 1‐Stellung durch eine Methyl‐, Äthyl‐ oder Phenylgruppe substituiert sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1968
1968
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 1 publication
1
15
0
1
Order By: Relevance
“…While it was already synthesized in 1963 by Ozegowski and Krebs [1] and in use for decades in Germany against a number of malignancies, it was only in 2008 that bendamustine was approved by the United States Food and Drug Administration (US FDA) for the treatment of chronic lymphocytic leukemia (CLL) and later for indolent B-cell non-Hodgkin's lymphoma (NHL) that has progressed during or following treatment with rituximab or a rituximab-containing regimen. To date, at least 80 clinical trials with bendamustine are active and recruiting patients [2], indicating that there is a lot of new interest in this rather old drug.…”
Section: Introductionmentioning
confidence: 99%
“…While it was already synthesized in 1963 by Ozegowski and Krebs [1] and in use for decades in Germany against a number of malignancies, it was only in 2008 that bendamustine was approved by the United States Food and Drug Administration (US FDA) for the treatment of chronic lymphocytic leukemia (CLL) and later for indolent B-cell non-Hodgkin's lymphoma (NHL) that has progressed during or following treatment with rituximab or a rituximab-containing regimen. To date, at least 80 clinical trials with bendamustine are active and recruiting patients [2], indicating that there is a lot of new interest in this rather old drug.…”
Section: Introductionmentioning
confidence: 99%
“…Bendamustine, 4‐[5‐[bis(2‐chloroethyl)amino]‐1‐methylbenzimidazol‐2‐yl]butanoic acid was first described in 1963 by Ozegowski and Krebs . It was used in East Germany for treating a variety of cancers and became available in West Germany after 1990.…”
Section: Treatment Componentsmentioning
confidence: 99%
“…Bendamustine originally was synthesized in 1963 at the Institute for Microbiology and Experimental Therapy in Jena in the former East German Democratic Republic (GDR) by Ozegowski and colleagues (3). In subsequent pre-clinical studies, bendamustine (at that time called IMET3393) displayed encouraging activities in hematopoietic cancers, such as myeloma models.…”
Section: Bendamustine: Revival Of An Old Drugmentioning
confidence: 99%
“…Previous studies, starting with the synthesis (3) and comparison with other nucleoside analogs (19) have suggested that this ring may act as purine analog. The chances, that a chemical addition of sugar to the benzimidazole ring followed by its phosphorylation to produce a purine nucleotide analog would occur in vivo, are extremely slim.…”
Section: Is Bendamustine Different From Other Alkylating Agents?mentioning
confidence: 99%